Under gas clouds effects shallow marine gas reservoir delineation - Purnomo, E.W. (European Association of Geoscientists and Engineers, EAGE, 2019)
New approach in seismic attribute and elastic impedance inversion has been used for identification of shallow gas clouds and characterization of deeper gas reservoir of under effected gas clouds shallow marine gas field, Malaysia. The novelty of the method, notably, it used Quality Factor Q and other thin-bed sensitive seismic attribute to constrain stochastic elastic impedance inversion. With the help of ANN and PCA, the inversion defined the relationship between input (seismic or Q, and other constraints) with the well log data. As the Q represented the porefluid characters, the method enable the direct definition of relationship between the earth elastic properties with Q data such that the estimation of elastic properties can be taken from Q data. Combination of inverted Vp/Vs, Variance and P-wave Quality Factor, Qp, is able to map the shallow gas clouds such that it can help the identifying potential drilling (shallow gas) hazard and study of petrophysical system in the area. The elastic inversion showed that the proposed inversion was able to delineate the considered thin gas sand reservoir from the field, conformable with log and seismic data. and significantly enhanced sand continuity beneath gas clouds. Â© 2019 EAGE-GSM 2nd Asia Pacific Meeting on Near Surface Geoscience and Engineering.All right reserved.